PENGETAHUAN DAN UPAYA PENCEGAHAN ANEMIA PADA REMAJA PUTRI SAAT MENSTRUASI - Aulia Rahmi; Meutia Zuhra; Feandi Putra; Husna Yeni (Jurnal Gema Keperawatan, 2026)
Anemia is a prevalent public health problem among adolescent girls, especially during menstruation, and may cause decreased concentration, fatigue, and lower academic performance. This condition can also affect physical growth and reproductive health in the long term if not properly addressed. The present study aims to describe the level of knowledge and preventive efforts related to anemia among adolescent girls at MTs Negeri 1 Kota Lhokseumawe. A descriptive study with a quantitative approach was conducted involving 75 respondents selected through random sampling. Data were obtained using a structured questionnaire consisting of 10 questions assessing knowledge and 6 questions concerning preventive actions. The findings revealed that most respondents had a moderate level of knowledge about anemia, with 39 respondents (52,0%) categorized as sufficient and 34 respondents (42,7%) as good. However, preventive efforts were still inadequate, with 46 respondents (61,3%) classified as poor. Common preventive actions included consuming nutritious foods rich in iron and taking iron supplements, yet these practices were often inconsistent. The results indicate a considerable gap between knowledge and the actual implementation of preventive behavior. Strengthening health education through school-based programs, counseling, and regular monitoring is crucial to enhance awareness, understanding, and adherence to anemia prevention practices among adolescent girls, particularly during menstruation.